Перспективи використання видів роду Platanus L. у зеленому будівництві - Grabovyi, V.M. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2000)
An analysis of possibilities of Platanus L. usage for formation of valuable decorative plantings is carried out on the basis of the data from literature and author’s researches. The assortment of varieties introduced in Ukraine is presented.